Perkembangan Ekonomi Indonesia Pasca Pandemi Covid-19 - Widiyantara, Gathot (LPPM STIE PPI, 2023)
Introduction/Main Objectives: The economy is a supporting factor for national development because good economic growth in a country can increase national development. Background Problems: Export activities were limited during the pandemic, and the value of exports fell due to the implementation of PSBB (Pembatasan Sosial Berskala Besar). Novelty: Continuing further research regarding Indonesia's economic development after the Covid-19 pandemic. Research Methods: This method uses an evaluation research method in the case study of Indonesia's economic growth after the Covid-19 pandemic. Finding/Results: Economic recovery occurs when economic growth increases, so an increase in export performance is needed. Conclusion: Increasing exports will cause an increase in domestic output, so increasing output will encourage the domestic economy in the future